Анализ современных тенденций развития конструкций силовых установок моноблочного типа для колесных боевых бронированных машин - Сядристый, М. А.; Федоренко, Е. В.; Воловик, Н. В.; Мормило, Я. М.; Рассказов, И. И. (НТУ "ХПИ", 2011)
The article gives analysis of powerpacks intended for modern wheeled armored fighting vehicles of the leading manufacturers with respect to convenience and speed of mounting/dismounting them on to the vehicles. The article also gives technical requirements for monoblock-type designs of powerpack for wheeled armored fighting vehicles.
Keywords: военная техника; боевая машина; бронированная машина; установки силовые